Cartographic Representation of Tectonic Activity Indicators to Valley Basins South of Kira's Mount by Using Geographic Information Systems - Al-Humairi, Mohammed (Al-Adab Journal, 2023)
The current study aims to use geographic information systems software, and topographical and geological maps in the process of derivation and cartographic representation of indicators of tectonic activity to valley basins south of Mount Kira, which are represented by indicators of stream length and degree of slope (SL) and the indicator of the ratio of the width of the valley floor to the height of the valley (VF), the topographic symmetry factor index (T), the asymmetry factor index (AF), the mountain front meander index (Smf), the basin shape index (Bs), and finally the relative tectonic activity index (Iat).It was revealed through the final classification of tectonic activity indicators that the ten basins of the valleys of the study area fall into three categories, which is a category with very high tectonic activity and includes the valleys of Wadi Batadim and Dar Halal. As for the second category, which is represented by high tectonic activity, it includes the basins of the valleys of Davro, Babak, and Kandalus. While the third category, which has moderate tectonic activity, includes the valleys of Al-Wala, Jalal, Jem Mashko, Asaki, and Horiz basins.